Ngangsu Tuking Karahayon Sabda Dalem. Berteologi Melalui Macapatan Kitab Suci sebagai Lectio Divina - Prabowo, Ditia (Perspektif, 2013)
The article describes that many Javanese Christians are practising the socalled Macapatan Kitab Suci, which is similar to the traditional Lectio Divina (Latin for “Divine Reading”). Similar to Lectio Divina, in Macapatan Kitab Suci the faithful Christians treat the Scriptures not only as holy texts to be studied, but primarily as the Living Word of God. By chanting the holy texts [which literally means Macapatan Kitab Suci], the faithfuls may come closer and ever more deeply immerse into the presence of the Divine. The traditional Lectio Divina has four steps, namely lectio, meditatio oratio, and contemplatio – read, meditate, pray and contemplate.Similar to Lectio Divina, by practising Macapatan Kitab Suci or chanting the Scriptures, the faithfuls gradually let themselves go of their own agendas and open to what God wants to say to them. The writer then argues that Macapatan Kitab Suci is another way of doing mission evangelization in the Javanese context.